Succinic acid production with Actinobacillus succinogenes: rate and yield analysis of chemostat and biofilm cultures - Brink, Hendrik Gideon (BioMed Central, 2014)
BACKGROUND: Succinic acid is well established as bio-based platform chemical with production quantities expecting to increase exponentially within the next decade. Actinobacillus succinogenes is by far the most studied wild organism for producing succinic acid and is known for high yield and titre during production on various sugars in batch culture. At low shear conditions continuous fermentation with A. succinogenes results in biofilm formation. In this study, a novel shear controlled fermenter was developed that enabled: 1) chemostat operation where self-immobilisation was opposed by high shear rates and, 2) in-situ removal of biofilm by increasing shear rates and subsequent analysis thereof. RESULTS: The volumetric productivity of the biofilm fermentations were an order of magnitude more than the chemostat runs. In addition the biofilm runs obtained substantially higher yields. Succinic acid to acetic acid ratios for chemostat runs were 1.28±0.2 g.g(-1), while the ratios for biofilm runs started at 2.4 g.g(-1) and increased up to 3.3 g.g(-1) as glucose consumption increased. This corresponded to an overall yield on glucose of 0.48±0.05 g.g(-1) for chemostat runs, while the yields varied between 0.63 g.g(-1) and 0.74 g.g(-1) for biofilm runs. Specific growth rates (μ) were shown to be severely inhibited by the formation of organic acids, with μ only 12% of μ(max) at a succinic acid titre of 7 g.L(-1). Maintenance production of succinic acid was shown to be dominant for the biofilm runs with cell based production rates (extracellular polymeric substance removed) decreasing as SA titre increases. CONCLUSIONS: The novel fermenter allowed for an in-depth bioreaction analysis of A. succinogenes. Biofilm cells achieve higher SA yields than suspended cells and allow for operation at higher succinic acid titre. Both growth and maintenance rates were shown to drastically decrease with succinic acid titre. The A. succinogenes biofilm process has vast potential, where self-induced high cell densities result in higher succinic acid productivity and yield.